2002
DOI: 10.1128/jcm.40.11.4143-4147.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Specific Detection of Mycobacterium tuberculosis from Acid-Fast Bacillus Smear-Positive Respiratory Specimens and BacT/ALERT MP Culture Bottles by Using Fluorogenic Probes and Real-Time PCR

Abstract: A real-time PCR assay using the LightCycler (LC) instrument for the specific identification of Mycobacterium tuberculosis complex (MTB) was employed to detect organisms in 135 acid-fast bacillus (AFB) smear-positive respiratory specimens and in 232 BacT/ALERT MP (MP) culture bottles of respiratory specimens. The LC PCR assay was directed at the amplification of the internal transcribed spacer region of the Mycobacterium genome with real-time detection using fluorescence resonance energy transfer probes specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 39 publications
1
49
0
2
Order By: Relevance
“…Other studies also reported false-negative results by RT-PCR in paucibacillary samples (Miller et al, 2002;Cleary et al, 2003;Lira et al, 2013). These authors observed an inversely proportional relationship between the C t values and the number of AFB detected in microscopy, as also encountered in our study (data not shown).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Other studies also reported false-negative results by RT-PCR in paucibacillary samples (Miller et al, 2002;Cleary et al, 2003;Lira et al, 2013). These authors observed an inversely proportional relationship between the C t values and the number of AFB detected in microscopy, as also encountered in our study (data not shown).…”
Section: Discussionsupporting
confidence: 76%
“…The use of RT-PCR for TB diagnosis has increased, as it has proven to be highly sensitive and specific for detection of the Mycobacterium tuberculosis complex (MTBC) directly in clinical samples or from culture isolates (García-Quintanilla et al, 2002;Miller et al, 2002;Broccolo et al, 2003;Cleary et al, 2003;Armand et al, 2011;Lira et al, 2013). Many regions of the mycobacterial genome have been used in molecular diagnosis of TB, such as IS6110, 16S rRNA, hsp65, rpoB, sdaA, devR and mpt64 (Manjunath et al, 1991;Lachnik et al, 2002;Kim et al, 2004;Chakravorty et al, 2005;Negi et al, 2007;Hwang et al, 2013;Nimesh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, with different targets, have reported similar results (Shrestha et al, 2003) and many have been designed as multiplex assays to differentiate Mtb complex from other non-tuberculosis mycobacteria based on melting curve analysis (Shrestha et al, 2003). Furthermore, these assays were often shown to be as sensitive and specific as the available commercial assays such as the Cobas Amplicor (Miller et al, 2002;Shrestha et al, 2003).…”
Section: Laboratory-developed Pcr Methodsmentioning
confidence: 68%
“…Several real-time PCR LDTs have been developed for diagnosis of pulmonary tuberculosis. In one of the earlier studies by Miller et al (Miller et al, 2002), a real-time PCR assay was developed on the LightCycler platform (Roche Diagnostics, Indianapolis, IN) with primers targeting the internal transcribed spacer region of the mycobacterium genome with specific hybridization probes designed for the detection of Mtb complex. The sensitivity and specificity of this assay for smear-positive respiratory specimens was 98.1% and 100% respectively with a turn-around time of less than 5 hours (Miller et al, 2002).…”
Section: Laboratory-developed Pcr Methodsmentioning
confidence: 99%
See 1 more Smart Citation